Human population genetics - Relethford, John. (Hoboken, N.J. : Wiley-Blackwell, 2012)
"Human Population Genetics will provide an introduction to mathematical population genetics, along with relevant examples from human (and some non-human primate) populations, and will also present concepts and methods of population genetics that are specific to the study of human populations. The purpose of this book is to provide a basic background text for advanced undergraduate and graduate students interesting in the mechanisms of human microevolution"--
Includes bibliographical references (p. 267-278) index.
Keywords: Human population genetics; SOCIAL SCIENCE / Anthropology / Physical